Prevalence and factors associated with riboflavin deficiency among Filipino pregnant women, 6th National Nutrition Survey (2007)
Prevalence of riboflavin deficiency among 547 Filipino pregnant women covered by the 2003, 6th National Nutrition Survey of the Food and Nutrition Research Institute- Department of Science and Technology (FNRI-DOST) was assessed using erythrocyte glutathione reductase activation coefficient (EGR-AC). The association of factors such as dietary intake, use of supplements, iron status using serum ferritin and some gynecological data such as gravida, parity and age of gestation and age and level of education of the mothers with riboflavin status were also determined. Results showed that based on the EGR-AC cut-off level of ≥1.30, the overall prevalence of riboflavin deficiency was 49.1% (95% CI: 45.1-53.4%). Classified by trimesters, the percentage prevalences were 35.3%, 44.4% and 58.7% for the 1st, 2nd and 3rd trimesters with corresponding mean EGR-ACs of 1.29 ± 0.02, 1.30 ± 0.01 and 1.38 ± 0.02, respectively. Based on non-consecutive two-day 24-hr recall, the overall mean dietary intake of riboflavin from food was 0.81 mg/day hardly reaching 50.0% of the requirement. Only 6.2% of the mothers had riboflavin intakes meeting 100% or more of the RNI. Dietary data also revealed inadequate intakes of iron, vitamin A and C, thiamin, energy and protein. When mothers were grouped according to use of supplements, those who reported not taking any supplement had significantly elevated EGR-AC of 1.38 with corresponding prevalence of 59.6% compared to the rate of 33.3% and mean EGR-AC of 1.26 among mothers who took supplements. Pregnant women with at least college education were less likely to become riboflavin deficient. Also, the presence of normal serum ferritin level was significantly associated with better riboflavin status. In contrast, pregnant women with higher gestational age, and high parity (≥ 4 parity) have higher risk of riboflavin deficiency with odd's ratios of 1.07 (95% CI: 1.03-1.10) and 1.11 (95% CI: 1.01-1.21), respectively. Considering the high prevalence of riboflavin deficiency among Filipino pregnant women, it is recommended that Filipino pregnant women should be motivated to take multivitamins with riboflavin because dietary intakes do not meet the recommended levels. Policy makers, clinician and nutritionist should plan and implement intervention programs addressing the riboflavin nutriture of pregnant women (e.g. in conjunction with iron supplementation).